EFEK PERPADUAN BEBERAPA TUMBUHAN LIAR DI SEKITAR AREA PERTANAMAN PADI DALAM MENARIK ARTHROPODA MUSUH ALAMI DAN HAMA - Addina, Lu’aili (El-Hayah : Jurnal Biologi, 2013)
This study aims to determine the interest Arthropoda against some wild mix consisting of Chromolaena odorata, Bidens pilosa., Echinochloa Cruss-galli, and Pistia stratiotes. This research is a semi experimental parameters observed were differences in the abundance of arthropods in each observation plot good plot consisting of some combination of wild plants (block refugia) and plot a block away from refugia based on spatial and temporal distribution. Observations using the "visual control" developed Freie and Manhart (1992). Achieved 9 order Arthropoda consists of 32 families were recorded visiting a mix of wild plants, the Coccinellidae, Carabidae, Staphylinidae, Chrysomelidae, Curculionidae, Coenagrionidae, Libellulidae, Tettigonidae, Gryllidae, Acrididae, Mantidae, Syrphidae, Drosophilidae, Tipulidae, Formicidae, Vespidae, Sphecidae, Ichneumonidae, Braconidae, Pyralidae, Papilionidae, Noctuidae, Nymphalidae, Alydidae, Pentatomidae, Reduviidae, Cicadellidae, Delphacidae, Flatidae, Tetragnathidae, and Oxyopidae. The mean abundance was highest in plots dominated by observation block refugia of the family Coccinellidae arthropods that act as natural enemies with a mean abundance reached 29 individuals per day. While the family Reduviidae which acts as a pest has the lowest with a mean abundance value of 1 individual per day. The analysis shows there are 6 families Arthropod natural enemies and pests that show distribution patterns are influenced by the presence of a mix of wild plants (the spatial distribution pattern) and different observation time (temporal distribution pattern), from the family Coccinellidae, Ichneumonidae, Braconidae, Acrididdae, Drosophilidae and Coreidae with a P value 0.05.